2016
DOI: 10.4049/jimmunol.1501175
|View full text |Cite
|
Sign up to set email alerts
|

Progression from Nonalcoholic Fatty Liver to Nonalcoholic Steatohepatitis Is Marked by a Higher Frequency of Th17 Cells in the Liver and an Increased Th17/Resting Regulatory T Cell Ratio in Peripheral Blood and in the Liver

Abstract: Nonalcoholic fatty liver disease is increasing in prevalence. It can be subdivided into nonalcoholic fatty liver (NAFL) and nonalcoholic steatohepatitis (NASH). Five to twenty percent of cases progress from NAFL to NASH. Increased hepatic Th17 cells and IL-17 expression were observed in NASH mice and patients, respectively. We analyzed CD4+ effector T cells and regulatory T cells (Tregs) from peripheral blood and livers of NAFL and NASH patients. A total of 51 NAFL patients, 30 NASH patients, 31 nonalcoholic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
239
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(280 citation statements)
references
References 29 publications
18
239
0
1
Order By: Relevance
“…In a study with 94 subjects (30 with NASH, 31 with NAFLD, and 43 healthy controls), patients with NASH (and in less degree with steatosis) had a lower frequency of T regulatory cells in peripheral blood, in comparison with controls (30). In addition, the progression from steatosis to NASH was marked by a higher frequency of Th17 cells in the liver and an increased Th17/resting T regulatory cell ratio in the liver and in peripheral blood (30). …”
Section: The Role Of Cellular Immune Imbalances In Nafldmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study with 94 subjects (30 with NASH, 31 with NAFLD, and 43 healthy controls), patients with NASH (and in less degree with steatosis) had a lower frequency of T regulatory cells in peripheral blood, in comparison with controls (30). In addition, the progression from steatosis to NASH was marked by a higher frequency of Th17 cells in the liver and an increased Th17/resting T regulatory cell ratio in the liver and in peripheral blood (30). …”
Section: The Role Of Cellular Immune Imbalances In Nafldmentioning
confidence: 98%
“…NASH and metabolic alterations occurred in mice-fed HFD, and Th17 cells (either AAT or liver-derived) positively correlated with NASH (60). Other studies have shown in parallel that the reduction, dysfunction, or disproportionate number of Treg cells contributes to the progression to NASH because Treg cells play a critical role in regulating the inflammatory processes in the liver (24, 29, 30). This cellular imbalance is accompanied by the activation of the IL-17 axis, and an increase of other pro-inflammatory cytokines such as IL-6, and TNF-α (42, 58); and its value has been highlighted by the demonstration that therapies targeted to reverse this imbalance have shown the potential to alleviate steatosis and the progression to NASH (32, 61, 62).…”
Section: The Role Of Cellular Immune Imbalances In Nafldmentioning
confidence: 99%
“…Furthermore, IL-17A−/− mice were resistant to the development of steatohepatitis, whereas wild-type mice showed progression from NAFL to NASH via the induction of IL-17 and downstream mediators [84]. A most recent study reports the progression from NAFL to NASH is marked by an increase of ratio of Th17/resting regulatory T cells (Tregs) in peripheral blood and liver [85]. …”
Section: Inflammatory Mediators and Immune Alterationsmentioning
confidence: 99%
“…Reduction in CD4 + CD25 high CD127 low Treg frequency has been described in patients with alcoholic hepatitis (10). Progression from non-alcoholic fatty liver to non-alcoholic steatohepatitis is characterized by a higher frequency of Th17 cells in the liver and an increased ratio of Th17/resting CD4 + CD45RA + CD25 high Treg in peripheral blood (11). We, and others, have reported that there is an increase in Treg frequency in parallel with effector immune cells in autoimmune liver diseases (AILD) (1215).…”
Section: Profile Of Regulatory T Cells In Liver Diseasesmentioning
confidence: 99%